تصميم وتنفيذ مرشح توافقي رقمي DMFللتتابع المباشر الشبه عشوائيPNDS في مستقبلات CDMA على خلفية الضجيج الأبيض الجمعي باستخدام التقنيات الرقمية الحديثة. - محمد مالك (Latakia University Journal -Engineering Sciences Series, 2016)
في هذه المقالة نتناول آلية ترشيح إشارة تتابع مباشر شبه عشوائي أساسي (تتابع مفيد للمشترك المطلوب) (Pseudo Noise Direct Sequence)PNDS في مستقبلات CDMA وذلك بشكل عملي على خلفية تتابعين مباشرين شبه عشوائيين غير أساسيين (تتابع معيق لمشترك غير مطلوب )مع الضجيج الأبيض الجمعي بواسطة مرشح توافقي رقمي DMF وفق خوارزمية الطيفي المجال الزمني لإشارة الدخل و الإشارة المرجعية(نسخة الإشارة) باستخدام شريحة رقمية من نوع: Cyclone II EP2C20F484C7 FPGA من شركة ALTERA المتوضعة على بورد التطوير والتعليم DE1 وفق البارامترات التالية: -تردد التقطيع 1MHz. -عرض بيت المعطيات 128µsec. -عرض الشريحة1µsec. -عامل الضغط (عامل كبت الضجيج)128. -نسبة مطال الإشارة إلى مطال الضجيج على دخل المرشح:. -عامل الربح بالمعالجة: . نتائج عمل المرشح تدرس باستخدام راسم إشارة رقمي لإشارة الدخل وإشارة الخرج من اجل عدة حالات لعدد التتابعات المباشرة الشبه عشوائية وحالة وجود الضجيج الأبيض الجمعي المؤثرة على الدخل. In this research, we study the mechanism of filtering the signal of direct pseudo random sequence in the receptors of (CDMA) depending on two nonessential direct pseudo random sequences with the additive white noise by digital matched filter according to the logarithm of convolution in the time domain of input signal and reference signals by using digital chip type of (FPGAII EP2C20F484C7) cyclone from the company of (ALTERA). This chip is located on the board of Education and Development according to these following parameters: - Chopping frequency IMHz / sampling frequency IMHz. - Width of data pulse 128 µsec. - Width of one chip / one section 1 µsec. - Ratio of signal amplitude to noise amplitude on the input of the filter 1/1=. - Factor of processing gain =101og128=21dB. The results of the operation of digital filter are studies by using Digital Signal Tracer for both input and output signals for many cases of direct pseudo random sequences numbers in addition to the case of existing of additive white noise which influences the input.